Analisis Pendapatan Dan Kelayakan Usaha DAMIU Di Desa Tambarana - Ni Kadek Ayu Sri Wida Adnyani; Yunus Sading; Edhi Taqwa; Andi Herman Jaya; Nuryana Haprin DJ Achmad (Penerbit Goodwood, 2025)
Purpose: This study aimed to analyze the income and feasibility of the refill drinking water depot industry in Tambarana Village, Poso Pesisir Utara District. The objective is to assess business viability, both theoretically and economically. Methodology/approach: A quantitative descriptive approach was used to collect primary data from business owners through interviews and field observations. Financial analysis was performed using the revenue-cost (R/C) ratio to determine business feasibility. Results/findings: The results indicate that the total monthly income from the refill drinking water depot industry in Tambarana Village reaches Rp. 10,578,728 or an average of Rp. 2,115,745 per business unit. The R/C ratio obtained was 1.68, which implies that the business is feasible to operate, as the ratio exceeds 1. This means that the revenue earned is greater than the total costs incurred. Conclusion: Based on the R/C ratio, the industry is considered theoretically feasible. However, in practical economic terms, the income generated is only sufficient to meet the basic daily needs of the entrepreneurs and has not yet reached a level that allows for business development or its expansion. Limitations: This study focused solely on a single village and did not compare similar businesses in other regions, which may limit the generalizability of the findings. Contribution: This study provides insight into the financial viability of small-scale water refill businesses in rural areas and can serve as a reference for local governments or stakeholders aiming to support microenterprises through training, capital assistance, or marketing strategies.